AN AFRICAN HERBAL PHARMACOPEIA COULD UNDERPIN THE MEDICINAL PLANT INDUSTRY ON THE AFRICAN CONTINENT - Gurib-Fakim, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Paper prepared and presented on behalf of the ’Association of African Medicinal Plants Standards – AAMPS’ Africa is a continent endowed with enormous wealth of plant resources. Over 5000 distinct species are known to occur in the forest regions alone and most of them have been used for several centuries in traditional medicine for the prevention and treatment of diseases. African traditional medicine is the oldest and perhaps the most diverse of all medicine systems. The biological and cultural diversity of Africa is reflected in the marked regional differences in healing practices and unfortunately the various systems are poorly recorded and remain so to this day. Yet ancient kingdoms and empires of Africa had extensively codified healing practices. African Materia Medica consists of a mixture of many elements and includes many potent herbs. Few of these are, however, yet recognised in modern pharmacopoeias. Exceptions are Strophanthus, Kola, Catharanthus and Harpagophytum which have been included in several western pharmacopoeias. Although there are several important research publications on medicinal plants from Africa, the study of African medicinal plants has remained fragmented and neglected as compared to India and China. To date Africa has only contributed 83 of the world’s 1100 leading commercial medicinal plants despite the fact that the Sub-Saharan region as well as the Indian Ocean Islands, contain approximately 60.000 plant species – roughly a quarter of the world’s total. The potential that this represents for the business and agricultural sectors is enormous but Africa will lag behind unless it prepares internationally recognised medicinal plant standards. The Medicinal Plants Forum for Commonwealth Africa held in Cape Town in 2000, highlighted the lack of suitable technical specifications and quality control standards as a major constraint to the African herbal industry. Moreover the lack of official recognition from governments generally has been the major handicap to what could become an important income and foreign exchange earner for the continent. A follow up meeting in 2005 witnessed the creation of the Association of African Medicinal Plants Standards (AAMPS) a non profit making company registered in Mauritius set up to implement recommendations outlined in the Centurion Declaration which advocated the preparation of an African Herbal Pharmacopoeia. Over 50 standards have since then been prepared by a team of internationally renowned experts covering most of the most important African medicinal plants. The Association hopes that the publication of these monographs will inter alia, increase Africa’s capacity to build a viable herbal industry incorporating Good Agricultural, Good Manufacturing and Good Laboratory Practices and above all increase the visibility of African Medicinal plants as a source of income generation. Since 2005, AAMPS has established itself as the leading organisation working on medicinal plant standards on the continent. A Scientific Advisory Committee has been established and a number of long term projects have been launched to enable AAMPS to become a self-sustaining entity. These include AAMPS Publishing, which will produce books, manuals and some simple merchandising products including possibly a photo-library service specialising in African medicinal plants and herbal products. AAMPS aims at providing also a laboratory and technical network and a Consultancy and Management Service. In collaboration with other international bodies such as the International Foundation for Sciences (IFS), AAMPS will today launch a joint Fellowship programme and award an annual AAMPS/IFS prize for lifetime achievements in the promotion of African medicinal and aromatic plants. More details on the services to be provided for AAMPS can be obtained form the website: http://www.aamps.org